2015
DOI: 10.1155/2015/896035
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Parameters Effects on Acoustic Absorption at Polymer Foam

Abstract: Polymer foams have acoustic absorption properties that play an important role in reducing noise level. When the skeleton is set to motion, it is necessary to use generalized Biot-Allard model which takes into account the deformation of the skeleton and the fluid and the interactions between them. The aim of this work is to study the quality of acoustic absorption in polyurethane foam and to show the importance of the structural vibration of this foam on the absorption by varying mechanical parameters (Young’s … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…However, beyond that, polyurethane foam also was often used as core material to make sandwich board [22,23] and honeycomb board structures [24], because of its good vibration absorption and isolation performance. To understand the vibration characteristics of foam materials, the researchers studied the density, strength, and viscoelasticity of foam materials [25,26]. Lyes Dib et al found through the 3D COMSOL Multiphysics that Young’s modulus, Poisson’s ratio, damping factor, and density of polyurethane foam would change the absorption coefficient, thereby affecting the sound absorption performance [25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, beyond that, polyurethane foam also was often used as core material to make sandwich board [22,23] and honeycomb board structures [24], because of its good vibration absorption and isolation performance. To understand the vibration characteristics of foam materials, the researchers studied the density, strength, and viscoelasticity of foam materials [25,26]. Lyes Dib et al found through the 3D COMSOL Multiphysics that Young’s modulus, Poisson’s ratio, damping factor, and density of polyurethane foam would change the absorption coefficient, thereby affecting the sound absorption performance [25].…”
Section: Introductionmentioning
confidence: 99%
“…To understand the vibration characteristics of foam materials, the researchers studied the density, strength, and viscoelasticity of foam materials [25,26]. Lyes Dib et al found through the 3D COMSOL Multiphysics that Young’s modulus, Poisson’s ratio, damping factor, and density of polyurethane foam would change the absorption coefficient, thereby affecting the sound absorption performance [25]. The method of finite element numerical simulation could be used to analyze the material properties of foam materials under the vibration environment.…”
Section: Introductionmentioning
confidence: 99%
“…If, during the acoustic propagation, the structure can no longer be considered rigid, for instance, in the case of the polyurethane foams that are used to infiltrate the samples, the formulation must be corrected [43]. According to the poroelastic Biot's theory [46,47], the surface impedance (Z) may be calculated using Equations ( 15) and ( 16) [48]:…”
Section: Resultsmentioning
confidence: 99%
“…The referred theory considers that the propagation by compression waves is due to three separate waves: fast (P 1 ) and slower (P 2 ) compression waves and a shear wave (S) [48]. Considering these facts, the surface impedance (Z) may be divided into four possible impedance combinations according to Equations ( 17) and (18).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, mechanical characterizations of the poroelastic materials (i.e., polyurethane foam, recycled rubber, polyurethane resin, etc.) have been comprehensivly analyzed [25,26,27,28]. The reference papers show the importance of structural vibration in polyurethane foam, as the characteristic impedance and propagation of constant absorption vary the mechanical parameters like density, Young’s modulus, Poisson’s coefficient, and the structural damping factor, all characteristics that have influence on resonance frequency absorption.…”
Section: Introductionmentioning
confidence: 99%